Comparison of newly diagnosed and relapsed patients with acute promyelocytic leukemia treated with arsenic trioxide: insight into mechanisms of resistance. - Ezhilarasi Chendamarai; Saravanan Ganesan; Ansu Abu Alex; Vandana Kamath; Sukesh C Nair; Arun Jose Nellickal; Nancy Beryl Janet; Vivi Srivastava; Kavitha M Lakshmi; Auro Viswabandya; Aby Abraham; Mohammed Aiyaz; et al. (PLoS ONE)
There is limited data on the clinical, cellular and molecular changes in relapsed acute promyeloytic leukemia (RAPL) in comparison with newly diagnosed cases (NAPL). We undertook a prospective study to compare NAPL and RAPL patients treated with arsenic trioxide (ATO) based regimens. 98 NAPL and 28 RAPL were enrolled in this study. RAPL patients had a significantly lower WBC count and higher platelet count at diagnosis. IC bleeds was significantly lower in RAPL cases (P=0.022). The ability of malignant promyelocytes to concentrate ATO intracellularly and their in-vitro IC50 to ATO was not significantly different between the two groups. Targeted NGS revealed PML B2 domain mutations in 4 (15.38%) of the RAPL subset and none were associated with secondary resistance to ATO. A microarray GEP revealed 1744 genes were 2 fold and above differentially expressed between the two groups. The most prominent differentially regulated pathways were cell adhesion (n=92), cell survival (n=50), immune regulation (n=74) and stem cell regulation (n=51). Consistent with the GEP data, immunophenotyping revealed significantly increased CD34 expression (P=0.001) in RAPL cases and there was in-vitro evidence of significant microenvironment mediated innate resistance (EM-DR) to ATO. Resistance and relapse following treatment with ATO is probably multi-factorial, mutations in PML B2 domain while seen only in RAPL may not be the major clinically relevant cause of subsequent relapses. In RAPL additional factors such as expansion of the leukemia initiating compartment along with EM-DR may contribute significantly to relapse following treatment with ATO based regimens.